2018
DOI: 10.21608/ejfsat.2018.5216.1025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatoprotective Effect of Propolis Against Sub-Chronic Diazinon Induced Hepatotoxicity

Abstract: Nowadays, the puplic health faces a major proplem of increased pesticides use with appearing of various side effects. One of the most commonly used is diazinon. It exerts its effects on variable tissues and cells including hepatocytes. This work aimed to study the tendency of diazinon to cause hepatic affection in rats and study the possible propolis protective role. We used 30 rats, divided into 4 groups; group Ia (-ve control); group Ib (+ve control, corn oil group); group II (propolis group; 400mg /kg/day o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…Serum ALP is used primarily as a biochemical marker of hepatic disease and bone activity, such as bone growth or osteosarcoma (Ochi et al, 2013). In this study, ALP reduction was observed over time, a significant difference in T3, which may indicate a beneficial action for the liver, as reported in a study that verified a propolis protective role in the tendency of diazinon to cause hepatic affection in rats (Mahmoud, Shalaby, 2018) and the hepatoprotective effect of red propolis by the induction of chronic experimental hepatic lesions in rodents (Silva et al,2019). However, these results should be studied further because ALP is known to distribute in various tissues, including the liver, bone, intestine, kidneys, mammary glands, and placenta (Ochi et al, 2013).…”
Section: Discussionsupporting
confidence: 57%
“…Serum ALP is used primarily as a biochemical marker of hepatic disease and bone activity, such as bone growth or osteosarcoma (Ochi et al, 2013). In this study, ALP reduction was observed over time, a significant difference in T3, which may indicate a beneficial action for the liver, as reported in a study that verified a propolis protective role in the tendency of diazinon to cause hepatic affection in rats (Mahmoud, Shalaby, 2018) and the hepatoprotective effect of red propolis by the induction of chronic experimental hepatic lesions in rodents (Silva et al,2019). However, these results should be studied further because ALP is known to distribute in various tissues, including the liver, bone, intestine, kidneys, mammary glands, and placenta (Ochi et al, 2013).…”
Section: Discussionsupporting
confidence: 57%
“…Diazinon induces histological alterations in the liver by lowering the capacity of antioxidant systems and increasing the levels of free radicals 17 . Research done by Mahmoud et al revealed that inhalation of Diazinon by male Wistar rats in their study increased the apoptosis in the developing hepatocytes 12 .…”
Section: Discussionmentioning
confidence: 82%
“…Morus nigra is a rich amalgam of polyphenols, flavonoids, and anthocyanins, which exert strong antioxidant activity. With the antioxidant properties, Morus nigra causes a protective action against the oxidative damage to the biomolecules as well as membranes resulting from the free radicals 11,12 . Flavonoids in Morus nigra exhibit a wide range of antioxidant, antimicrobial, antiinflammatory, anti-cancer, anti-radiation properties and have a protective action against oxidative damage and hepatoprotective effects 13 .…”
Section: Introductionmentioning
confidence: 99%
“…The pervasive use of pesticides in agriculture significantly contributes to environmental pollution due to residual contamination. In particular, insecticides from the organophosphorus class are among the most frequently utilized [ 1 ]. Diazinon (DZN) is a highly popular organophosphate pesticide.…”
Section: Introductionmentioning
confidence: 99%